Pengaruh Penetapan Harga Transfer, Kepemilikan Keluarga, Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak - Gina, Erin Rista; Pramono, Nugroho Heri (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to gather empirical evidence on the impact of transfer pricing, family ownership, and sales growth on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This study uses a quantitative approach with secondary data obtained from the companies' annual financial reports. The population consisted of 83 companies, and the sample selection was carried out using a purposive sampling technique based on certain criteria, resulting in 10 companies as samples observed for five years, with a total of 50 observations. Data analysis was performed using panel data regression, and the model test results indicated that the fixed effect model was the best model. Data processing was carried out using EViews version 13 and Microsoft Excel. The results show that simultaneously, transfer pricing, family ownership, and sales growth influence tax avoidance. Partially, transfer pricing and sales growth have a significant effect, while family ownership does not show a significant effect. These findings indicate that some companies utilize certain strategies to reduce tax burdens, so it is hoped that they can be considered by regulators in designing more targeted tax policies.